Breviscapine remodels myocardial glucose and lipid metabolism by regulating serotonin to alleviate doxorubicin-induced cardiotoxicity - Li, Meng-Jiao; Sun, Wen-She; Yuan, Yang; Zhang, Yu-Kun; Lu, Qi; Gao, Yuan-Zhen; Ye, Ting; Xing, Dong-Ming (Frontiers in Pharmacology, 2022)
Aims The broad-spectrum anticancer drug doxorubicin (DOX) is associated with a high incidence of cardiotoxicity, which severely affects the clinical application of the drug and patients' quality of life. Here we assess how DOX modulates myocardial energy and contractile function and could aid the development of relevant protective drugs. Methods Mice were subjected to doxorubicin and breviscapine treatment. Cardiac function was analyzed by echocardiography and DOX-mediated signaling was assessed in isolated cardiomyocytes. The dual cardio-protective and anti-tumor action of breviscapine were assessed in mice breast tumor models. Results We found that DOX disrupts myocardial energy metabolism by decreasing glucose uptake and increasing fatty acid oxidation, leading to a decrease in ATP production rate, an increase in oxygen consumption rate, oxidative stress, and further energy deficits to enhance myocardial fatty acid uptake and drive DIC development. Interestingly, breviscapine increases the efficiency of ATP production and restores myocardial energy homeostasis by modulating the serotonin-glucose-myocardial PI3K/AKT loop, increasing glucose utilization by the heart, and reducing lipid oxidation. It enhances mitochondrial autophagy via the PINK1/Parkin pathway, eliminates damaged mitochondrial accumulation caused by DOX, reduces the degree of cardiac fibrosis and inflammation, and restores cardiac micro-environmental homeostasis. Importantly, its low inflammation levels reduce myeloid immunosuppressive cell infiltration, and this effect is synergistic with the anti-tumor effect of DOX. Conclusions Our findings suggest that disruption of the cardiac metabolic network by DOX is an important driver of its cardiotoxicity and that serotonin is an important regulator of myocardial glucose and lipid metabolism. Myocardial energy homeostasis and timely clearance of damaged mitochondria synergistically contribute to the prevention of anthracycline-induced cardiotoxicity and improve the efficiency of tumor treatment.